Water use in bean and cowpea: efficiency or effective use of water? - Polanía Perdomo, José A.; Vadez, Vincent; Rao, Idupulapati M.; Cajiao V., César Hernando; Beebe, Stephen E. (International Center for Tropical Agriculture, 2017)
Water stress is one of the major abiotic stress limitations for grain legume production in smallholder agricultural systems. Phenotypic characterization of water consumption by different species of legumes and genotypes within them plays a key role in adaptation to drought. Dynamics of water use may differ depending on the origin and evolution of the species of legume and the agro-climatic conditions faced by the legumes. The supply of nitrogen from symbiotic fixation is also critical for filling seeds and is even more limiting than water in bean, but not in cowpea.